Sex and ideology: liberal and conservative responses to scandal. Issue 2 (3rd April 2022) - Saxton, Gregory W.; Barnes, Tiffany D.
ABSTRACT: Research finds citizens are less likely to penalize politicians implicated in sex scandals compared to corruption. Still, observational data reveals that some politicians have better luck surviving sex scandals than others. Do voters punish politicians for sex scandals? We argue yes – some do. Whereas liberals are inclined to view sex scandals as personal matters – unrelated to a politician's job performance – conservatives are more likely to view sex scandals as moral outrages that disregard traditional values and threaten the social order. Conservatives are thus less forgiving of sex scandals than liberals, especially when women politicians are implicated. Using evidence from a survey experiment in the US designed to isolate the effect of scandal type (corruption vs. sex) and candidate sex, we investigate heterogeneous effects by political ideology. We find that liberals tend to be forgiving of sex scandals, but not corruption. Conservatives, by contrast, punish men's sex scandals on par with men's involvement in corruption. And, conservatives assign women a penalty bonus for either type of scandal. That is, they are significantly more likely than liberals to punish women for involvement in either type of scandal – sex or corruption.